LEGAL PROTECTION FOR MOSLEM CONSUMERS ON HALAL GUARANTEE OF FOOD PRODUCTS IN INDONESIA - Redhita Febri Athifah (FH 16 UMY 109, 2016)
Moslem consumer protection becomes important in Indonesia. The most of Indonesian’s consumers are Moslem, So many Product with unlabeled halal make the Moslem consume difficult in determining the product consumed whether it is halal or not. Based on the data of Research Institute for Foods, Drugs and Cosmetics (LPPOM MUI) in 2014 there were so many products without halal label. This research is a normative legal research and a library research which applies statute and conceptual approaches. The data gathered from the review of the literature or library materials related to the problem or research materials that comprises of a premier law, secondary and tertiary. The research found that Indonesian’s Moslem consumer should get the rights and get more protection against the assurance halal of food product as defined in the Law No. 8 of 1999. Meanwhile, The Responsibility of businessman on the product, can be found in Article 19 Paragraph (1) and (5) as well as Article 28 of Law No. 8 in 1999 on Consumer Protection. For those who want to make the certificate halal label in their products, the costumer should have to follow some processes or stages to obtain the halal certificate issued by the MUI. The responsibility for businessman who was tagging without procedure in halal labels could be deemed in the provisions of the legislation included in Law No. 8 of 1999 on Consumer Protection, Act No. 7 of 1996 on Food and The Government Regulation No. 69 of 1999 on food label and advertisement. Keywords: Legal Protection, Muslim Consumer, Halal Product, Indonesia